2015
DOI: 10.1016/j.jobaz.2015.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical composition and nutritional value of Streptocephalus simplex as live feed in ornamental fish culture

Abstract: A feed trail was conducted to evaluate the efficiency of Streptocephalus simplex as a live feed in freshwater ornamental fish culture. The efficiency of live feed was compared with that of artificial/pellet diet to determine the growth rate biochemical parameters and carotenoid concentration of Carassius auratus for a period of 45 days. As a result the proximate composition on the S. simplex indicates that they are rich in protein, lipids, essential amino acids and fatty acids. Availability of these growth fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Many studies have shown the use of the brine shrimp Artemia (Leach 1819) as an excellent larval diet in aquaculture (Agh, Noori, Irani, Van Stappen & Sorgeloos, ; Simhachalam, Kumar & Rao, ). However, the use of Artemia in freshwater aquaculture is hampered by the organism's osmoregulatory adaptation to its natural environment (saline habitats).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown the use of the brine shrimp Artemia (Leach 1819) as an excellent larval diet in aquaculture (Agh, Noori, Irani, Van Stappen & Sorgeloos, ; Simhachalam, Kumar & Rao, ). However, the use of Artemia in freshwater aquaculture is hampered by the organism's osmoregulatory adaptation to its natural environment (saline habitats).…”
Section: Introductionmentioning
confidence: 99%
“…Most fish larvae require planktonic organisms as their first feed and record better growth and survival rates when fed these organisms rather than artificial diets [5,10,[23][24][25][26]. Several factors explain these results: the structure and digestibility of the protein, presence of exogenous enzymes, chemical stimuli, adequate size, and slow movements of the prey that facilitate its ingestion and digestion, characteristics that meet the requirements of the larva [27].…”
Section: Introductionmentioning
confidence: 99%
“…Larvae of many aquatic species either have complete dependence on zooplankton live food as a basal diet, or they have significantly better performance when started on live food [ 1 ]. Live food is commonly regarded as “living capsules of nutrition”, rich in proteins, vitamins, carbohydrates, minerals, amino acids, and fatty acids [ 2 ]. As a superior nutritional prey, some zooplankton contain high levels of digestive enzymes [ 3 ] and are capable of producing appetite-stimulating effects on larvae [ 4 ].…”
Section: Introductionmentioning
confidence: 99%